Życie i Zagłada w Hrubieszowie w oczach młodej warszawianki - Libionka, Dariusz; Kopciowski, Adam (Zagłada Żydów. Studia i Materiały, 2007)
This text deals with the situation of the Jewish population of Hrubieszów between autumn 1941 and the first deportation action in June 1942. The author of the testimony is a woman by the name Dychterman, who came to Hrubieszów from the Warsaw ghetto. During the “action” she managed to leave for Warsaw. This testimony was written two weeks later, i.e. in late June 1942 by staff members of Ringelblum’s Archive. It stands out among other testimonies from Hrubieszów in the Warsaw Ghetto Archives, as it is full of details and complex description. It also contains an interesting description of the Jewish community in the town, the living conditions and its everyday life. It also contains data of the Judenrat members as well as observations on the Christian-Jewish relations (i.e. between Jews and Poles or Ukrainians). The second part of the testimony describes the first liquidation action in Hrubieszów, the extermination action and the reactions of the Judenrat and that of the population towards the resettlement. The fate of the author remains unknown. Most likely she died during the “Great Action” in the Warsaw ghetto. This account has been used by historians, but never previously published.